Identification of a novel aminoglycoside nucleotidyltransferase gene in Morganella morganii from farm sewage - Junwan Lu; Jing Wang; Mengdi Gao; Kexin Zhou; Jialei Liang; Chunhan Song; Xuying He; Chaoqun Liu; Huiyue Feng; Wei Pan; Qiyu Bao; Chunxia Yan; et al. (BMC Microbiology)
Abstract Background Aminoglycosides are important broad-spectrum antimicrobial agents. When combined with β-lactam drugs, these agents can be used to treat severe infections such as those causing sepsis. Identifying additional resistance mechanisms will guarantee the successful application of aminoglycoside agents in clinical practice. Methods The isolate Morganella morganii A19 was obtained from a sewage sample from an animal farm by means of agar plate streaking. The agar dilution method was used to determine the minimum inhibitory concentrations (MICs) of the antimicrobial agents. Cloning of the predicted resistance gene was conducted, and its resistance function was assessed through MIC testing. The protein was expressed in E. coli, and the kinetic parameters were quantified. The analysis of novel resistance gene-related sequences, including their structures and evolutionary relationships, was performed using bioinformatic tools. Results In Morganella morganii A19, a newly discovered chromosome-encoded aminoglycoside resistance gene named aadA37 was identified and characterized. The protein AadA37 exhibited the highest amino acid identity (57.14%) with the functionally characterized aminoglycoside adenylyltransferase AadA33. aadA37 confers resistance to spectinomycin, streptomycin and ribostamycin, and enzyme kinetic analysis also demonstrated that it had adenosine transfer activities against spectinomycin and streptomycin, with k cat/K m values of 0.66 × 103 M− 1 s− 1 and 1.63 × 103 M− 1 s− 1, respectively. The aadA37 gene and its homologs were not related to any mobile genetic element (MGE), and they were all found to be encoded on the chromosomes of the M. morganii strains. Conclusion A novel aminoglycoside resistance gene was identified from an environmental bacterium and characterized in this work. Identifying new resistance mechanisms will aid in the effective clinical use of antimicrobial agents for treating infectious diseases caused by pathogens harboring the same resistance genes.